An Investigation of Pain Beliefs, Pain Coping, and Spiritual Well-Being in Surgical Patients - Gülnar, Emel (Journal of religion and health, 2022)
This study investigated pain beliefs, pain coping, and spiritual well-being in surgical patients. The study adopted a cross-sectional, descriptive, and correlational research design. The sample consisted of 213 voluntary patients admitted to a surgery clinic between April and November 2019. Data were collected using a demographic characteristics questionnaire, the Functional Assessment of Chronic Illness Therapy-Spiritual Well-Being Scale-12 item (FACIT-Sp-12), the Pain Beliefs Questionnaire (PBQ), and the Pain Coping Questionnaire (PCQ). Number, percentage, mean, and Spearman’s correlation were used for analysis. Participants had a total FACIT-Sp-12 score of 25.99 ± 8.43. They had a mean PBQ "organic beliefs" and "psychological beliefs" subscale score of 4.44 ± 0.64 and 4.96 ± 0.68, respectively. They had a mean PCQ "self-management," "helplessness," "conscious coping attempts," and "medical remedies" subscale score of 15.83 ± 6.15, 9.41 ± 4.63, 8.72 ± 3.66, and 7.46 ± 5.33, respectively. Spiritual well-being was weakly and positively (r = 0.445, p < 0.000) correlated with self-management and moderately and negatively correlated (r = − 0.528, p < 0.000) with helplessness. Participants with higher organic and psychological beliefs had lower spiritual well-being. The results indicate that nurses should evaluate both pain and spiritual well-being in patients.